Implementation Of The Stad (Student Team Achievement Divisions) Method To Improve Bottom Passing Technique Capability In Volleyball Games At Mi Mambaul Ulum Kasri, Bululawang District, Malang District - Setiawan, Rizki Nur; Ernata, Yusvidha; Sudarsono, Sudarsono; Kusmawati, Wiwik (Jurnal Ilmiah Mandala Education (JIME), 2024)
Students' passing skills are still less than optimal, as evidenced by the still quite high number of failed passes in class VI in MI Mambaul Ulum Kasri, Bululawang District, Malang Regency. Teachers have never used the STAD (Student Team Achievement Divisions) method. to improve students' ability to make down passes. This research aims to determine the ability of down passing techniques in volleyball games at MI Mambaul Ulum Kasri, Bululawang District, Malang Regency using the STAD type cooperative method. It can be concluded that learning using the STAD type cooperative method is able to improve the ability of lower passing techniques in volleyball games at MI Mambaul Ulum Kasri, Bululawang District, Malang Regency.